Scientific impact and social interest of Artificial Intelligence research: analysis based on data from Dimensions - Andrade Gontijo, Marília Catarina; Ferreira de Araújo, Ronaldo; Travieso Rodríguez, Críspulo (Revista General de Información y Documentación, 2021)
This article studies scientific production on Artificial Intelligence dealing with both bibliographic and citation issues and its public and social interest. From an exploratory methodological approach, it is examined the academic impact, according to citation indicators, and online attention, according to altmetrics indicators. It was collected a total of 7.453 open access articles published between 2012 and 2019. Data sources for the data collecting were Dimensions and Altmetric Explorer. Results show that, on one hand, academic impact had a medium scope, as more than a half - 53,3% of the articles included - had at least one cite. On the other hand, online attention can be considered low, as only 32.3% of the articles obtained mentions in social media. It was confirmed that research on Artificial Intelligence is mainly interdisciplinary; besides, it was proved that using bibliometrics and altmetrics jointly have a complementary value in order to analyze the whole impact of the scientific literature.